A method for preparing Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material
Through the preparation method of Na2MoO4 and nitrogen-sulfur-doped carbon-coated layered oxide cathode material, the shortcomings in energy density, cycle stability and cost of the existing sodium ion battery cathode materials are solved, and high energy density, excellent cycle performance and low cost are achieved.
Patent Information
- Application Number
- CN202310590456.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-05-24
AI Technical Summary
The existing sodium ion battery positive electrode materials have shortcomings in terms of energy density, cycle stability and cost, especially the P2 type manganese-based layered oxide materials are limited by problems such as low energy density, poor cycle performance and high potential side reactions.
The preparation method of Na2MoO4 and nitrogen-sulphur-doped carbon-coated layered oxide positive electrode material is adopted, and the material particles with high conductivity and high stability are formed through ultrasonic stirring and heat treatment.
The electronic and ionic conductivity of the material is improved, high reversible capacity and excellent cycling stability are obtained, while reducing the cost of material preparation.
Smart Images

Figure CN116654997B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material. Background Art
[0002] With the continuous consumption of non-renewable energy and the intensification of environmental pollution problems, clean and renewable energy has received widespread attention. As an efficient and clean energy carrier, rechargeable secondary batteries can effectively alleviate the current energy and environmental problems. Lithium-ion batteries (LIBs) were developed and commercialized by Sony in 1991. LIBs have the advantages of high energy density, long service life, low self-discharge rate, low maintenance cost, and good safety, and are widely used in portable electronic products. Although the technology of lithium-ion batteries is mature, lithium-ion batteries still have problems in terms of safety, life, poor low-temperature performance, and high cost. In addition, with the widespread use of electric vehicles and portable electronic devices, the demand for lithium continues to increase, and the limited reserves of lithium ore have further pushed up the price of lithium-ion batteries. Therefore, the search for lower-cost batteries has received increasing attention. Due to the abundant reserves of sodium elements in nature, people have studied them extensively. However, due to the relatively low operating voltage compared with lithium systems, the energy density and cycle stability of sodium-ion batteries are still far from meeting the needs of electric vehicles and energy storage systems. A key issue for SIBs to meet the growing requirements of electronic products is to find positive electrode materials with high energy density and excellent cycle performance. Transition metal oxide materials have the advantages of simple synthesis, adjustable composition, and high power density. The general structure of layered oxides is Na x MO2 (M is mainly one or more transition metal elements) is composed of repeated sheets of edge-shared MO6 octahedral transition metal layers, with sodium ions located between the transition metal layers. According to the different sodium coordination environments and oxygen stacking sequences, layered oxides are mainly divided into P2, O2, O3 and P3. Due to the cost-effectiveness of Na and Mn elements, Na x MnO2 is a highly regarded manganese-based cathode material for sodium-ion batteries. P2-type manganese-based layered oxides are considered to be one of the most promising cathode materials for sodium-ion batteries due to their high theoretical specific capacity, suitable operating voltage, and abundant raw materials. However, this type of compound has obvious disadvantages: (1) Mn 3+ / Mn 4+ The working voltage of the redox couple is low, resulting in low energy density of the material, and Mn 3+(1) When working at low potential, it is easy to induce Jahn-Teller distortion, resulting in irreversible capacity decay; (2) The structural evolution of the material is complex during the redox reaction, and it is easy to undergo irreversible phase change when working at high potential, resulting in poor cycle and rate performance; (3) Working at high potential is easy to cause serious material / electrolyte side reactions, causing dissolution of electrode materials and continuous consumption of electrolyte; (4) When the material is stored in the air, Na2CO3 or NaHCO3 compounds are easily formed on the surface, which damages its capacity, cycle and rate performance, and increases storage and transportation costs. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention provides a method for preparing Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode materials. The synthesis method has a simple process and good controllability. The raw materials are cheap and widely available. The obtained material particles have uniform particle size and high crystallinity, which improves the electronic and ionic conductivity of the material, obtains high reversible capacity and excellent cycle stability, thereby reducing the cost of material preparation and improving the electrochemical performance of the material.
[0004] The technical solution adopted by the present invention to solve the above technical problems is:
[0005] A method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material comprises the following steps:
[0006] (1) preparing powders of an iron source, a copper source, a manganese source and a nickel source in a molar ratio of 3:2:13:2, and mixing them uniformly to obtain material A;
[0007] (2) ball milling material A and a sodium source at 400 rpm to obtain a fully mixed slurry, and drying the slurry in a vacuum drying oven at 60-80° C. for 10-12 h to prepare a precursor B;
[0008] (3) Precursor B is heated and then cooled to room temperature, the powder is ball-milled at 400-500 rpm for 10-12 h, and then sieved through 280 mesh to obtain NaFCMN layered oxide positive electrode material;
[0009] (4) mixing the prepared NaFCMN material, the carbon source, and ammonium molybdate with an inorganic substance and an organic solvent in a mass ratio of 20:200:1, performing ultrasonic stirring, and removing the organic solvent to obtain a mixture;
[0010] (5) The mixture in the above step (4) is heated under a mixed atmosphere, cooled to room temperature, washed by centrifugation with 1-1.5 mol / L hydrochloric acid, and dried to obtain a layered oxide positive electrode material co-coated with Na2MoO4 and nitrogen-sulfur-doped carbon, denoted as Na 0.67 Fe 0.15 Cu 0.1 Mn0.65 Ni 0.1 O2@Na2MoO4-N,SC.
[0011] The iron source in step (1) is a mixture of Fe2O3 and Fe3O4, and the molar ratio of Fe2O3 to Fe3O4 is (2-3):1.
[0012] The copper source in step (1) is a mixture of CuO and Cu(OH)2, and the molar ratio of CuO to Cu(OH)2 is (2.5-3):1.
[0013] The manganese source in step (1) is a mixture of Mn2O3 and Mn(OH)2, and the molar ratio of Mn2O3 to Mn(OH)2 is (1-2):1.
[0014] The nickel source in step (1) is a mixture of NiO and Ni(OH)2, and the molar ratio of NiO to Ni(OH)2 is (2-3):1.
[0015] The sodium source in step (2) is a mixture of Na2CO3, Na2C2O4 and NaOH, and the molar ratio of Na2CO3, Na2C2O4 and NaOH is (9-10):0.6:0.4; the molar ratio of the amount of sodium source added to the total amount of iron source, copper source, manganese source and nickel source added in the precursor B is 1:1.
[0016] The heating in step (3) is specifically to heat the material to 500-550°C at a heating rate of 5-8°C / min in an air atmosphere, keep the temperature for 4-5 hours, then heat the material to 850-900°C, and keep the temperature for 11-12 hours.
[0017] The carbon source in step (4) is a mixture of petroleum asphalt, high-temperature coal tar, melamine and thiourea, and the mass ratio of petroleum asphalt, high-temperature coal tar, melamine and thiourea is 3:(2-3):3:2.
[0018] The inorganic substance in step (4) is a mixture of NaCl and nano-MgO, the mass ratio of NaCl to nano-MgO is 5:1, and the mass ratio of the inorganic substance to the total amount of NaFCMN material, carbon source and ammonium molybdate in (4) is (18-20):1.
[0019] The organic solvent in step (4) is a mixture of toluene, isopropanol and anhydrous ethanol, and the volume ratio is 7:1:2, and the ratio (mL:g) to the inorganic substance in (4) is 1:1.
[0020] The ultrasonic stirring in step (4) specifically includes ultrasonic dispersion for 1-1.5 hours and then strong magnetic stirring for 10-12 hours.
[0021] The mixed atmosphere in step (5) is a mixed gas of NH3 and N2, and the volume ratio of NH3 to N2 is 5:95.
[0022] The heating in step (5) is to raise the temperature to 350-400° C. and keep the temperature for 4-4.5 hours.
[0023] The drying in step (5) is vacuum drying, and the drying time is 10-12 hours.
[0024] A sodium ion battery layered oxide positive electrode material, specifically Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC was prepared by the above preparation method.
[0025] The application of the sodium ion battery layered oxide positive electrode material comprises the following steps:
[0026] The sodium ion battery layered oxide positive electrode material Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC was used as the research electrode and the metal sodium sheet as the counter electrode to assemble a CR2025 type button sodium ion battery in a glove box filled with argon, and the charge and discharge cycle was carried out in the potential range of 2-4.2 V. At a current of 0.1C, the first reversible specific capacity was 170.76mAh / g, and the capacity retention rate reached 75.55% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0027] Compared with the prior art, the present invention has the following technical effects:
[0028] 1. The present invention uses nitrogen- and sulfur-doped carbon and sodium molybdate to co-coat the positive electrode material, wherein the synergistic effect of the doping of N and S elements and the three-dimensional cross-linked carbon network significantly improves the conductivity of the electrode material, (NH4)6Mo7O 24 ·4H2O combines with the residual alkali on the surface of the layered oxide to form Na2MoO4, which can not only effectively improve the problems of the layered oxide being difficult to preserve and prone to side reactions caused by the presence of residual alkali, but also react with HF to finally form MoO through the intermediate of the H2MoO4 (MoO3·H2O) layer. 3-x F 2xThe co-coating layer not only provides a highly conductive nanolayer between particles, giving the particles low charge transfer resistance and high conductivity, but also hinders direct contact between particles and electrolyte, reducing the corrosion of the electrolyte to the particles.
[0029] 2. The material synthesized by the present invention has uniform particles, good dispersibility and high crystallinity, which is beneficial to improving the electrochemical properties of the material.
[0030] 3. The material obtained by the present invention has excellent rate performance and stable cycle life when applied to sodium ion batteries. The preparation process is simple and relatively mature, and has certain industrial feasibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the layered oxide positive electrode material obtained in Example 1 of the present invention.
[0032] Figure 2 This is the cycle performance curve of the layered oxide positive electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] Example 1
[0034] Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide cathode material Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 The preparation method of O2@Na2MoO4-N,SC, the specific steps are as follows:
[0035] (1) 0.00185 mol Fe2O3, 0.0007 mol Fe3O4, 0.003 mol CuO, 0.001 mol Cu(OH)2, 0.0087 mol Mn2O3, 0.0086 mol Mn(OH)2, 0.003 mol NiO and 0.001 mol Ni(OH)2 are made into powders, and the powders are mixed uniformly to obtain material A;
[0036] (2) Material A was ball-milled with 0.036 mol Na2CO3, 0.0024 mol Na2C2O4 and 0.0016 mol NaOH at 400 rpm for 4 h to obtain a fully mixed slurry, which was then dried in a vacuum oven at 80°C for 12 h to prepare precursor B;
[0037] (3) Precursor B was heated to 500°C at a rate of 5°C / min in an air atmosphere, kept at this temperature for 4 h, then heated to 850°C, kept at this temperature for 12 h, and then cooled to room temperature. The powder was ball-milled at 400 rpm for 10 h and sieved through 280 mesh to obtain Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2 (hereinafter referred to as NaFCMN) layered oxide positive electrode material;
[0038] (4) Add 0.1 g of the prepared NaFCMN material, 0.3 g of petroleum asphalt, 0.2 g of high-temperature coal tar, 0.3 g of melamine, 0.2 g of thiourea, 0.005 g of ammonium molybdate, 20 g of a mixture of NaCl and nano-MgO, and 20 mL of a mixture of toluene, isopropanol, and anhydrous ethanol in a volume ratio of 7:1:2 into a 50 mL round-bottom flask, wherein the mass ratio of the mixture of NaFCMN material, petroleum asphalt, high-temperature coal tar, melamine, thiourea, ammonium molybdate, NaCl, and nano-MgO is 5:1, and ultrasonically disperse for 1.5 h and then strongly magnetically stir for 12 h, and remove toluene, isopropanol, and anhydrous ethanol by rotary evaporation to obtain a mixture;
[0039] (5) The mixture after the removal of toluene, isopropanol and anhydrous ethanol was transferred into a tube furnace, heated to 350°C in a mixed gas of NH3 and N2 with a volume ratio of 5:95, and kept at this temperature for 4 hours. After cooling to room temperature with the furnace, NaCl and nano-MgO in the mixture were removed by using 1 mol / L hydrochloric acid. After centrifugal washing, the mixture was vacuum dried for 12 hours to obtain Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC cathode material (see Figure 1 ).
[0040] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and the charge and discharge cycle was carried out in the potential range of 2-4.2V. Figure 2 As shown, at a current of 0.1C, the first reversible specific capacity is 170.76 mAh / g, and the capacity retention rate reaches 75.55% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0041] Example 2
[0042] (1) 0.0018 mol Fe2O3, 0.0008 mol Fe3O4, 0.0028 mol CuO, 0.0012 mol Cu(OH)2, 0.0087 mol Mn2O3, 0.0086 mol Mn(OH)2, 0.0025 mol NiO and 0.0015 mol Ni(OH)2 are made into powders, and the powders are uniformly mixed to obtain material A;
[0043] (2) Material A was ball-milled with 0.0365 mol Na2CO3, 0.0022 mol Na2C2O4 and 0.0013 mol NaOH at 400 rpm for 4 h to obtain a fully mixed slurry, which was then dried in a vacuum oven at 80°C for 12 h to prepare precursor B;
[0044] (3) Precursor B was heated to 550°C at a heating rate of 5°C / min in an air atmosphere, kept at this temperature for 4 hours, then heated to 850°C, kept at this temperature for 12 hours, and then cooled to room temperature. The powder was ball-milled at 400 rpm for 10 hours and sieved through 280 mesh to obtain NaFCMN layered oxide positive electrode material;
[0045] (4) Add 0.1 g of the prepared NaFCMN material, 0.3 g of petroleum asphalt, 0.2 g of high-temperature coal tar, 0.3 g of melamine, 0.2 g of thiourea, 0.005 g of ammonium molybdate, 20 g of a mixture of NaCl and nano-MgO, and 20 mL of a mixture of toluene, isopropanol, and anhydrous ethanol in a volume ratio of 7:1:2 into a 50 mL round-bottom flask, wherein the mass ratio of the mixture of NaFCMN material, petroleum asphalt, high-temperature coal tar, melamine, thiourea, ammonium molybdate, NaCl, and nano-MgO is 5:1, and ultrasonically disperse for 1.5 h and then strongly magnetically stir for 12 h, and remove toluene, isopropanol, and anhydrous ethanol by rotary evaporation to obtain a mixture;
[0046] (5) The mixture after the removal of toluene, isopropanol and anhydrous ethanol was transferred into a tube furnace, heated to 400°C in a mixed gas of NH3 and N2 with a volume ratio of 5:95, and kept at a constant temperature for 4 hours. After cooling to room temperature with the furnace, 1.5 mol / L hydrochloric acid was used to remove NaCl and nano-MgO in the mixture. After centrifugal washing, it was vacuum dried for 12 hours to obtain Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC positive electrode material.
[0047] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and charged and discharged in the potential range of 2-4.2 V. At a current of 0.1C, the first reversible specific capacity was 149.49 mAh / g, and the capacity retention rate reached 73.79% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0048] Example 3
[0049] (1) 0.0018 mol Fe2O3, 0.0008 mol Fe3O4, 0.003 mol CuO, 0.001 mol Cu(OH)2, 0.0104 mol Mn2O3, 0.0052 mol Mn(OH)2, 0.003 mol NiO and 0.001 mol Ni(OH)2 are made into powders, and the powders are uniformly mixed to obtain material A;
[0050] (2) Material A was ball-milled with 0.0357 mol Na2CO3, 0.0026 mol Na2C2O4 and 0.0017 mol NaOH at 400 rpm for 4 h to obtain a fully mixed slurry, which was then dried in a vacuum oven at 80°C for 12 h to prepare precursor B;
[0051] (3) Precursor B was heated to 500°C at a heating rate of 8°C / min in an air atmosphere, kept at this temperature for 4 hours, then heated to 850°C, kept at this temperature for 12 hours, and then cooled to room temperature. The powder was ball-milled at 400 rpm for 10 hours and sieved through 280 mesh to obtain NaFCMN layered oxide positive electrode material;
[0052] (4) Add 0.1 g of the prepared NaFCMN material, 0.28 g of petroleum asphalt, 0.24 g of high-temperature coal tar, 0.28 g of melamine, 0.2 g of thiourea, 0.005 g of ammonium molybdate, 20 g of a mixture of NaCl and nano-MgO, and 20 mL of a mixture of toluene, isopropanol, and anhydrous ethanol in a volume ratio of 7:1:2 into a 50 mL round-bottom flask, wherein the mass ratio of the mixture of NaFCMN material, petroleum asphalt, high-temperature coal tar, melamine, thiourea, ammonium molybdate, NaCl, and nano-MgO is 5:1, and ultrasonically disperse for 1.5 h and then strongly magnetically stir for 12 h, and remove toluene, isopropanol, and anhydrous ethanol by rotary evaporation to obtain a mixture;
[0053] (5) The mixture after the removal of toluene, isopropanol and anhydrous ethanol was transferred into a tube furnace, heated to 350°C in a mixed gas of NH3 and N2 with a volume ratio of 5:95, and kept at this temperature for 4 hours. After cooling to room temperature with the furnace, 1.5 mol / L hydrochloric acid was used to remove NaCl and nano-MgO in the mixture. After centrifugal washing, the mixture was vacuum dried for 12 hours to obtain Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC positive electrode material.
[0054] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and charged and discharged in the potential range of 2-4.2 V. At a current of 0.1C, the first reversible specific capacity was 157.98 mAh / g, and the capacity retention rate reached 74.01% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0055] Example 4
[0056] (1) 0.00185 mol Fe2O3, 0.0007 mol Fe3O4, 0.003 mol CuO, 0.001 mol Cu(OH)2, 0.0087 mol Mn2O3, 0.0086 mol Mn(OH)2, 0.0025 mol NiO and 0.0015 mol Ni(OH)2 are made into powders, and the powders are uniformly mixed to obtain material A;
[0057] (2) Material A was ball-milled with 0.036 mol Na2CO3, 0.0024 mol Na2C2O4 and 0.0016 mol NaOH at 400 rpm for 4 h to obtain a fully mixed slurry, which was then dried in a vacuum oven at 80°C for 12 h to prepare precursor B;
[0058] (3) Precursor B was heated to 550°C at a heating rate of 5°C / min in an air atmosphere, kept at this temperature for 4 hours, then heated to 850°C, kept at this temperature for 12 hours, and then cooled to room temperature. The powder was ball-milled at 400 rpm for 10 hours and sieved through 280 mesh to obtain NaFCMN layered oxide positive electrode material;
[0059] (4) Add 0.1 g of the prepared NaFCMN material, 0.3 g of petroleum asphalt, 0.2 g of high-temperature coal tar, 0.3 g of melamine, 0.2 g of thiourea, 0.005 g of ammonium molybdate, 20 g of a mixture of NaCl and nano-MgO, and 20 mL of a mixture of toluene, isopropanol, and anhydrous ethanol in a volume ratio of 7:1:2 into a 50 mL round-bottom flask, wherein the mass ratio of the mixture of NaFCMN material, petroleum asphalt, high-temperature coal tar, melamine, thiourea, ammonium molybdate, NaCl, and nano-MgO is 5:1, and ultrasonically disperse for 1.5 h and then strongly magnetically stir for 12 h, and remove toluene, isopropanol, and anhydrous ethanol by rotary evaporation to obtain a mixture;
[0060] (5) The mixture after the removal of toluene, isopropanol and anhydrous ethanol was transferred into a tube furnace, heated to 350°C in a mixed gas of NH3 and N2 with a volume ratio of 5:95, and kept at this temperature for 4.5 hours. After cooling to room temperature with the furnace, 1 mol / L hydrochloric acid was used to remove NaCl and nano-MgO in the mixture. After centrifugal washing, the mixture was vacuum dried for 12 hours to obtain Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC positive electrode material.
[0061] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and charged and discharged in the potential range of 2-4.2 V. At a current of 0.1C, the first reversible specific capacity was 168.98 mAh / g, and the capacity retention rate reached 75.4% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0062] Example 5
[0063] (1) 0.00185 mol Fe2O3, 0.0007 mol Fe3O4, 0.0028 mol CuO, 0.0012 mol Cu(OH)2, 0.01 mol Mn2O3, 0.006 mol Mn(OH)2, 0.003 mol NiO and 0.001 mol Ni(OH)2 are made into powders, and the powders are uniformly mixed to obtain material A;
[0064] (2) Material A was ball-milled with 0.0365 mol Na2CO3, 0.0022 mol Na2C2O4 and 0.0013 mol NaOH at 400 rpm for 4 h to obtain a fully mixed slurry, which was then dried in a vacuum oven at 80°C for 12 h to prepare precursor B;
[0065] (3) Precursor B was heated to 500°C at a heating rate of 5°C / min in an air atmosphere, kept at this temperature for 4 hours, then heated to 850°C, kept at this temperature for 12 hours, and then cooled to room temperature. The powder was ball-milled at 400 rpm for 10 hours and sieved through 280 mesh to obtain NaFCMN layered oxide positive electrode material;
[0066] (4) Add 0.1 g of the prepared NaFCMN material, 0.3 g of petroleum asphalt, 0.2 g of high-temperature coal tar, 0.3 g of melamine, 0.2 g of thiourea, 0.005 g of ammonium molybdate, 20 g of a mixture of NaCl and nano-MgO, and 20 mL of a mixture of toluene, isopropanol, and anhydrous ethanol in a volume ratio of 7:1:2 into a 50 mL round-bottom flask, wherein the mass ratio of the mixture of NaFCMN material, petroleum asphalt, high-temperature coal tar, melamine, thiourea, ammonium molybdate, NaCl, and nano-MgO is 5:1, and ultrasonically disperse for 1.5 h and then strongly magnetically stir for 12 h, and remove toluene, isopropanol, and anhydrous ethanol by rotary evaporation to obtain a mixture;
[0067] (5) The mixture after the removal of toluene, isopropanol and anhydrous ethanol was transferred into a tube furnace, heated to 300°C in a mixed gas of NH3 and N2 with a volume ratio of 5:95, and kept at a constant temperature for 4.5 hours. After cooling to room temperature with the furnace, 1.5 mol / L hydrochloric acid was used to remove NaCl and nano-MgO in the mixture. After centrifugal washing, it was vacuum dried for 12 hours to obtain Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC positive electrode material.
[0068] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and charged and discharged in the potential range of 2-4.2 V. At a current of 0.1C, the first reversible specific capacity was 158.06 mAh / g, and the capacity retention rate reached 74.8% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0069] Example 6
[0070] (1) 0.0018 mol Fe2O3, 0.0008 mol Fe3O4, 0.003 mol CuO, 0.001 mol Cu(OH)2, 0.0087 mol Mn2O3, 0.0087 mol Mn(OH)2, 0.002 mol NiO and 0.002 mol Ni(OH)2 are made into powders and uniformly mixed to obtain material A;
[0071] (2) Material A was ball-milled with 0.0357 mol Na2CO3, 0.0026 mol Na2C2O4 and 0.0017 mol NaOH at 400 rpm for 4 h to obtain a fully mixed slurry, which was then dried in a vacuum oven at 80°C for 12 h to prepare precursor B;
[0072] (3) Precursor B was heated to 500°C at a heating rate of 5°C / min in an air atmosphere, kept at this temperature for 4 hours, then heated to 850°C, kept at this temperature for 12 hours, and then cooled to room temperature. The powder was ball-milled at 400 rpm for 10 hours and sieved through 280 mesh to obtain NaFCMN layered oxide positive electrode material;
[0073] (4) Add 0.1 g of the prepared NaFCMN material, 0.27 g of petroleum asphalt, 0.27 g of high-temperature coal tar, 0.27 g of melamine, 0.19 g of thiourea, 0.005 g of ammonium molybdate, 20 g of a mixture of NaCl and nano-MgO, and 20 mL of a mixture of toluene, isopropanol, and anhydrous ethanol in a volume ratio of 7:1:2 into a 50 mL round-bottom flask, wherein the mass ratio of the mixture of NaFCMN material, petroleum asphalt, high-temperature coal tar, melamine, thiourea, ammonium molybdate, NaCl, and nano-MgO is 5:1, and ultrasonically disperse for 1.5 h and then strongly magnetically stir for 12 h, and remove toluene, isopropanol, and anhydrous ethanol by rotary evaporation to obtain a mixture;
[0074] (5) The mixture after the removal of toluene, isopropanol and anhydrous ethanol was transferred into a tube furnace, heated to 350°C in a mixed gas of NH3 and N2 with a volume ratio of 5:95, and kept at this temperature for 4 hours. After cooling to room temperature with the furnace, NaCl and nano-MgO in the mixture were removed by using 1 mol / L hydrochloric acid. After centrifugal washing, the mixture was vacuum dried for 12 hours to obtain Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC positive electrode material.
[0075] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and charged and discharged in the potential range of 2-4.2 V. At a current of 0.1C, the first reversible specific capacity was 166.24 mAh / g, and the capacity retention rate reached 74.27% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0076] Example 7
[0077] (1) 0.0018 mol Fe2O3, 0.0008 mol Fe3O4, 0.003 mol CuO, 0.001 mol Cu(OH)2, 0.001 mol Mn2O3, 0.006 mol Mn(OH)2, 0.003 mol NiO and 0.001 mol Ni(OH)2 are made into powders, and the powders are mixed uniformly to obtain material A;
[0078] (2) Material A was ball-milled with 0.0357 mol Na2CO3, 0.0026 mol Na2C2O4 and 0.0017 mol NaOH at 400 rpm for 4 h to obtain a fully mixed slurry, which was then dried in a vacuum oven at 80°C for 12 h to prepare precursor B;
[0079] (3) Precursor B was heated to 550°C at a heating rate of 5°C / min in an air atmosphere, kept at this temperature for 4 hours, then heated to 850°C, kept at this temperature for 12 hours, and then cooled to room temperature. The powder was ball-milled at 400 rpm for 10 hours and sieved through 280 mesh to obtain NaFCMN layered oxide positive electrode material;
[0080] (4) Add 0.1 g of the prepared NaFCMN material, 0.3 g of petroleum asphalt, 0.2 g of high-temperature coal tar, 0.3 g of melamine, 0.2 g of thiourea, 0.005 g of ammonium molybdate, 20 g of a mixture of NaCl and nano-MgO, and 20 mL of a mixture of toluene, isopropanol, and anhydrous ethanol in a volume ratio of 7:1:2 into a 50 mL round-bottom flask, wherein the mass ratio of the mixture of NaFCMN material, petroleum asphalt, high-temperature coal tar, melamine, thiourea, ammonium molybdate, NaCl, and nano-MgO is 5:1, and ultrasonically disperse for 1.5 h and then strongly magnetically stir for 12 h, and remove toluene, isopropanol, and anhydrous ethanol by rotary evaporation to obtain a mixture;
[0081] (5) The mixture after the removal of toluene, isopropanol and anhydrous ethanol was transferred into a tube furnace, heated to 350°C in a mixed gas of NH3 and N2 with a volume ratio of 5:95, and kept at this temperature for 4.5 hours. After cooling to room temperature with the furnace, 1.5 mol / L hydrochloric acid was used to remove NaCl and nano-MgO in the mixture. After centrifugal washing, the mixture was vacuum dried for 12 hours to obtain Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC positive electrode material.
[0082] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and charged and discharged in the potential range of 2-4.2 V. At a current of 0.1C, the first reversible specific capacity was 162.49 mAh / g, and the capacity retention rate reached 73.52% after 100 cycles, showing excellent charge and discharge performance and cycle stability.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material, characterized in that: The following steps are involved: (1) preparing powders of an iron source, a copper source, a manganese source and a nickel source in a molar ratio of 3:2:13:2, and mixing them uniformly to obtain material A; The iron source is a mixture of Fe2O3 and Fe3O4; The copper source is a mixture of CuO and Cu(OH)2; The manganese source is a mixture of Mn2O3 and Mn(OH)2; The nickel source is a mixture of NiO and Ni(OH)2; (2) Grinding material A and a sodium source in a ball mill to obtain a fully mixed slurry, and drying it in a vacuum drying oven to obtain a precursor B; The sodium source is a mixture of Na2CO3, Na2C2O4 and NaOH; In the precursor B, the molar ratio of the amount of the sodium source added to the total amount of the iron source, the copper source, the manganese source and the nickel source added is 1:1; (3) heating the precursor B, then cooling it to room temperature, grinding the powder in a ball mill, and sieving it through a 280-mesh sieve to obtain a NaFCMN layered oxide positive electrode material; (4) mixing the prepared NaFCMN material, the carbon source, and ammonium molybdate with an inorganic substance and an organic solvent in a mass ratio of 20:200:1, performing ultrasonic stirring, and removing the organic solvent to obtain a mixture; The carbon source is a mixture of petroleum asphalt, high-temperature coal asphalt, melamine and thiourea, the inorganic substance is a mixture of NaCl and nano-MgO, and the organic solvent is a mixture of toluene, isopropanol and anhydrous ethanol; (5) The mixture in the above step (4) is heated under a mixed atmosphere, cooled to room temperature, washed by centrifugation with hydrochloric acid, and dried to obtain a layered oxide positive electrode material co-coated with Na2MoO4 and nitrogen-sulfur-doped carbon; the mixed atmosphere is a mixed gas of NH3 and N2.
2. The method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material according to claim 1, characterized in that: In the steps (1)-(2), the molar ratio of Fe2O3 and Fe3O4 is (2-3):1; the molar ratio of CuO and Cu(OH)2 is (2.5-3):1; the molar ratio of Mn2O3 and Mn(OH)2 is (1-2):1; the molar ratio of NiO and Ni(OH)2 is (2-3):1; and the molar ratio of the mixture of Na2CO3, Na2C2O4 and NaOH is (9-10):0.6:0.
4.
3. The method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material according to claim 1, characterized in that: In the step (3), the precursor B is heated, specifically, in an air atmosphere, the temperature is increased to 500-550°C at a heating rate of 5-8°C / min, kept at this temperature for 4-5 hours, and then increased to 850-900°C, and kept at this temperature for 11-12 hours.
4. The method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material according to claim 1, characterized in that: In the step (4), the mass ratio of petroleum asphalt, high-temperature coal asphalt, melamine and thiourea is 3:(2-3):3:
2.
5. The method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material according to claim 1, characterized in that: In the step (4), the mass ratio of NaCl to nano-MgO is 5:1, and the mass ratio of the inorganic matter to the total amount of NaFCMN material, carbon source and ammonium molybdate in (4) is (18-20):
1.
6. The method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material according to claim 1, characterized in that: The volume ratio of toluene, isopropanol and anhydrous ethanol in the step (4) is 7:1:2, and the ratio (mL:g) of the organic solvent to the inorganic substance in the step (4) is 1:
1.
7. The method for preparing a Na2MoO4 and nitrogen-sulfur-doped carbon co-coated layered oxide positive electrode material according to claim 1, characterized in that: In the step (5), the volume ratio of NH3 to N2 is 5:
95.
8. The method for preparing a Na2MoO4 and nitrogen-sulfur doped carbon co-coated layered oxide positive electrode material according to claim 1, characterized in that: The heating in step (5) is to raise the temperature to 350-400° C. and then keep the temperature for 4-4.5 hours.
9. A sodium ion battery layered oxide positive electrode material, specifically Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC is prepared by the preparation method described in any one of claims 1-8.
10. Use of the sodium ion battery layered oxide positive electrode material according to claim 9 in a sodium ion battery, characterized in that: The following steps are involved: The sodium ion battery layered oxide positive electrode material Na 0.67 Fe 0.15 Cu 0.1 Mn 0.65 Ni 0.1 O2@Na2MoO4-N,SC was used as the research electrode and the metal sodium sheet as the counter electrode. They were assembled into a CR2025 button-type sodium-ion battery in an argon-filled glove box and subjected to charge and discharge cycles in the potential range of 2-4.2V.
Citation Information
Patent Citations
Zinc-site sodium-copper co-doped synergistic nitrogen-sulfur doped carbon-coated modified zinc titanate negative electrode material and preparation method and application thereof
CN110581273A
Preparation method and application of nitrogen-sulfur-doped carbon-loaded Fe7S8 battery negative electrode material
CN113224291A